Role of TDM-Based Dose Adjustments For AC/T Regimen Drugs Used In Breast Carcinoma - Smitha Sarah Thambi; Balasubramanian Arul; Ramalingam Kothai (Revista Electronica de Veterinaria, 2024)
Breast cancer, a prevalent and significant health issue among women, is influenced by genetic, environmental, and lifestyle factors. Treatment often involves the AC/T regimen (Adriamycin, Cyclophosphamide, and Paclitaxel), which presents dosage challenges due to toxicity and therapeutic window limitations. This review focuses on the role of Therapeutic Drug Monitoring (TDM) in optimizing AC/T regimen doses to enhance efficacy and reduce side effects. TDM's impact on improving clinical outcomes is discussed, especially with targeted therapies like tyrosine kinase inhibitors and immunosuppressants. Adriamycin's DNA intercalation, Cyclophosphamide’s DNA alkylation, and Paclitaxel’s microtubule stabilization illustrate varied mechanisms of action that benefit from TDM for dose personalization. This analysis highlights TDM's potential in reducing adverse effects while maximizing therapeutic impact in breast cancer treatment.